Comparison of non-linear models for describing growth of Guzerat beef cattle females - Oliveira, H. N. de; Lobo, R. B.; Pereira, C. S. (Empresa Brasil Pesq Agropec, 2000)
Data on growth and reproduction of 573 females Guzerat beef cattle born between 1961 and 1985, at Fazenda Canoas, located in the county of Curvelo, MG, Brazil, were used to obtain a growth pattern for the breed, through the use of a mathematical model. Weight-age data, collected up to 1992, were used to fit five nonlinear models: Brody, Bertalanffy, Logistic, Gompertz, and Richard. Estimated assyntotic weight and growth rate were, respectively, for Brody model 464.49 and 0.046; for Bertalanffy model 453.18 and 0.065; for Logistic model 447.05 and 0.085; for Gompertz model 449.89 and 0.075, and for Richards model 458.26 and 0.055. Richards model presented computational difficulty to fit the data. Other models showed good fit to the data, and presented little variations on the criteria chosen. Bertalanffy model showed a better goodness of fit on the set of criteria and was the choice to describe the growth patterns of Guzerat cattle.
Keywords: weight; maturation; growth rate; mathematical models